Novice Explanations Of Hurricane Formation Offer Insights Into Scientific Literacy And The Development Of Expert-Like Conceptions (Journal of Astronomy & Earth Sciences Education, 2016)
The ability to explain scientific phenomena is a key feature of scientific literacy, and engaging students’ prior knowledge, especially their alternate conceptions, is an effective strategy for enhancing scientific literacy and developing expertise. The gap in knowledge about the alternate conceptions that novices have about many of Earth’s complex phenomena (National Research Council, 2012), however, makes this type of engagement in geoscience courses challenging. This study helps to fill this gap by identifying and describing how novices to geoscience explain a complex scientific phenomenon, hurricane formation. Using a pragmatism methodology, 326 students in introductory-level geoscience courses at two public universities in the United States of America, in Georgia (n=168) and Nebraska (n=158), were surveyed. The questionnaire was designed to target and collect novices’ explanations of a single complex Earth phenomenon – hurricane formation. Constant comparative analyses of textual content and diagrams revealed a variety of alternate conceptions. The data suggests that novices seldom invoke scientific first principles, which students matriculating through the education system are expected to learn before college, in their explanations. Two theoretical models synthesize the alternate conceptions and illustrate pathways of conceptual change along which students might move from more novice-like to more expert-like ways of scientific thinking. Our findings provide a basis for the development of instructional activities that aid students in developing more expertlike conceptions of hurricane formation and other complex Earth phenomena.
Keywords: Geoscience Education Research; Meteorology Education; Scientific Literacy; Misconceptions; Novice-To-Expert; Conceptual Change